Navigating Tolerance: An Analysis of Public Responses on Social Media to the MUI Fatwa on Interfaith Greetings - Abdullah, Fuady (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2025)
This study aims to analyze people's responses in social media as a space of social interaction to the fatwa of the Indonesian Ulema Council (MUI) on interfaith greetings that has been considered controversial.  The fatwa asserts that using interfaith greetings is not in line with Islamic principles of legitimate tolerance. Given the urgency to discuss this debate in Indonesia's pluralistic society, this study utilized a mixed-methods approach. Data was collected using crawling techniques from X social media platform and analysed with R and Python to perform topic modelling and sentiment analysis, then related tweets were qualitatively analysed. In the various topics discussed, the analysis shows that, despite the controversy and its diminishing regulative authority, MUI's role as a charismatic, traditional and ethical religious authority is still widely recognized. This research contributes to the understanding of how fatwas are perceived and debated in social media spaces, highlighting the need for MUI to constantly offer religious guidance that observes Islamic tradition while being socially relevant. The study underscores the importance of MUI's active participation in the ongoing discourse on religious tolerance and moderation in Indonesian society.